Afiksasi sebagai Representasi Kritik Sosial dalam Lirik Lagu "Pesta Para Babi Pembangunan" : Perspektif Etika Sosial Islam - Hosniyeh Hosniyeh (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2026)
This study aims to describe the forms of affixation in the lyrics of the song "Pesta Para Babi Pembangunan" (Feast of the Development Pigs), analyze the function of affixation in representing social criticism, and interpret the meaning of such criticism from the perspective of Islamic social ethics. The study employs a qualitative descriptive method, utilizing the song's lyrics as the data source. Data were collected through listening, reading, and note-taking techniques, and subsequently analyzed by identifying, classifying, and interpreting the forms and functions of affixation based on the lyrical context and the perspective of Islamic social ethics. The results indicate that the affixation in the lyrics encompasses prefixes, confixes, and suffixes—specifically the loan element -isasi (-ization). These forms function not only as word-formation processes but also contribute to representing social criticism. The prefix di- in words such as dibakar (burned), dibelah (split), dijual (sold), and dikubur (buried) represents the position of nature and society as the affected parties, whereas forms such as mengatur (regulating), pembangunan (development), perlindungan (protection), kolonisasi (colonization), and legalisasi (legalization) represent domination, policies, and mechanisms of power. This social criticism can be interpreted through the principles of al-'adl (justice), amanah (trustworthiness/stewardship), maslahah (public interest/welfare), and hurriyah (freedom). The study concludes that affixation in the song lyrics plays a role in constructing a critique of development that is oriented toward the interests of power and capital. The perspective of Islamic social ethics asserts that development should ideally be grounded in justice, trustworthiness, public welfare, and community participation. Key words: Morphology; social criticism; Islamic social ethics; language; affixation